A Comparison of Survival Outcomes in Advanced Serous Ovarian Cancer Patients Treated With Primary Debulking Surgery Versus Neoadjuvant Chemotherapy. Issue 4 (May 2017) - May, Taymaa; Comeau, Robyn; Sun, Ping; Kotsopoulos, Joanne; Narod, Steven A.; Rosen, Barry; Ghatage, Prafull
Abstract : Objective: The management of women with advanced-stage serous ovarian cancer includes a combination of surgery and chemotherapy. The choice of treatment with primary debulking surgery or neoadjuvant chemotherapy varies by institution. The objective of this study was to report 5-year survival outcomes for ovarian cancer patients treated at a single institution with primary debulking surgery or neoadjuvant chemotherapy. Methods: This study included a retrospective chart review of 303 patients with stage IIIC or IV serous ovarian carcinoma diagnosed in Calgary, Canada. The patients were categorized into 1 of the 2 treatment arms: primary debulking surgery or neoadjuvant chemotherapy. The 5-year ovarian cancer–specific survival rates were estimated using Kaplan-Meier curves. Results: Among the 303 eligible patients, 142 patients (47%) underwent primary debulking surgery, and 161 patients (53%) were treated with neoadjuvant chemotherapy. Five-year survival was better for patients undergoing primary debulking surgery (39%) than for patients who received neoadjuvant chemotherapy (27%; P = 0.02). Women with no residual disease experienced better overall survival than those with any residual disease (47% vs. 26%, respectively; P = 0.0002). This difference was significant for those who had primary debulking surgery ( P = 0.0004) but not for the patients who received neoadjuvant chemotherapy ( P = 0.09). Women who received intraperitoneal chemotherapy had better overall survival as compared with patients who received intravenous chemotherapy (44% vs 30%, respectively; P = 0.002). Conclusions: Our findings suggest that among women with no residual disease, survival is better among those who undergo primary debulking surgery than treatment with neoadjuvant chemotherapy. The latter should be reserved for women who are deemed not to be candidates for primary debulking surgery. Abstract : Supplemental digital content is available in the text.